2020
DOI: 10.1002/bmc.4921
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitative determination of liraglutide and insulin degludec in rat plasma by liquid chromatography–tandem mass spectrometry method and its application

Abstract: A simple, fast and high‐throughput LC–tandem mass spectrometry method was developed and validated to simultaneously measure liraglutide and insulin degludec in rat plasma. After protein precipitation, plasma samples were subjected to gradient elution using an InertSustain Bio C18 column with 1000/20/1 water/acetonitrile/formic acid (v/v/v) and 1000/1 acetonitrile/formic acid (v/v) as the mobile phase. The method was validated from 1.00 to 500 ng/mL of liraglutide and insulin degludec. Further, the extraction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The t 1/2 generated by TCA-RA method was within 5.40–6.43 h, which is longer than that of Degludec as reported to be 2.9 h and 2.3 h in rats. 34 , 35 The results also indicated that INS061 should possess a longer in vivo duration compared to Degludec, which is a strong evidence for its long-acting effects. In addition, the long-acting efficacy of INS601 on glucose lowering in STZ-induced diabetic rats further supported its prolonged duration in vivo.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The t 1/2 generated by TCA-RA method was within 5.40–6.43 h, which is longer than that of Degludec as reported to be 2.9 h and 2.3 h in rats. 34 , 35 The results also indicated that INS061 should possess a longer in vivo duration compared to Degludec, which is a strong evidence for its long-acting effects. In addition, the long-acting efficacy of INS601 on glucose lowering in STZ-induced diabetic rats further supported its prolonged duration in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…Whether INS061 is superior to Degludec, in terms of efficacy and the duration of action in the human body, requires future clinical investigation. However, according to the comparison of PK behaviors of Degludec in rats and humans reported in the literatures, 34,35,41 we are confident that INS061 is a potential effective and long-acting insulin analogue.…”
Section: Discussionmentioning
confidence: 85%
“…Extraction recovery was evaluated using six replicates of LQC, MQC, and HQC concentration levels. It was determined by comparing the peak area of the analytes in plasma spiked samples before and after extraction (Zhai et al, 2020; Zhu et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…As the molecular weight of liraglutide is large (m.w. = 3751.2), multiply charged precursor ions are often selected for MRM analysis (Dong et al 2018;Meng et al 2017;Sauter et al 2019;Zhai et al 2020). In the present study, the most abundant precursor ion in the positive Q1 mass scan spectrum was [M + 4H] 4+ at m/z 938.5 for liraglutide and [M + 4H] 4+ at m/z 1029.4 for IS (semaglutide).…”
Section: Lc-ms/ms Conditionsmentioning
confidence: 99%
“…Recent advances in LC-MS/MS have been overcoming its limitations of poor ionization, significant endogenous interference, and low sensitivity in the bioanalysis of peptides and proteins (Dong et al 2018;Meng et al 2017;Pinho et al 2019;Ewles and Goodwin 2011). There are several LC-MS/MS methods available for the determination of liraglutide in the plasma (Dong et al 2018;Meng et al 2017;Sauter et al 2019;Zhai et al 2020). However, no LC-MS/MS methods have been reported to determine liraglutide concentrations in the tissues.…”
Section: Introductionmentioning
confidence: 99%